Systematic Literature Review: Determinant of Islamic Bank Performance (IBP) - Suro, Lulu Ilmang (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2024)
Performance is a benchmark for the level of success achieved by the company. Research on sharia banking performance still requires a lot of further discussion. Most previous research only focused on financial aspects. This research aims to review literature regarding factors that influence Islamic banking performance (IBP), financial factors as measured by profitability, liquidity, and activity ratios, as well as other supporting factors. This study used a systematic literature review (SLR) method combined with bibliometric analysis. SLR is an approach to reviewing articles in a systematic and organised manner, aiming to increase the depth of research to make it more comprehensive and balanced. The results of this research are that most of the proxies for IBP are measured using profitability, namely ROA. The better the company’s asset management, the impact it will have on improving bank performance. NPF also has an impact on bank performance and is widely used to assess performance. The lower the NPF ratio, the more favourable it is. This means that the bank is able to manage its credit appropriately. Apart from good performance, banks also carry out CSR activities, where in Sharia banking, zakat is distributed. This research provides updates regarding more varied methods and variables in assessing the relationship between each variable and bank performance, both based on the literature review carried out. Future researchers can add several non-financial factors that are related to bank performance.